2011
DOI: 10.1142/s1793042111004319
|View full text |Cite
|
Sign up to set email alerts
|

THE SUM OF DIGITS OF n AND n2

Abstract: Let s q (n) denote the sum of the digits in the q-ary expansion of an integer n. In 2005, Melfi examined the structure of n such that s 2 (n) = s 2 (n 2 ). We extend this study to the more general case of generic q and polynomials p(n), and obtain, in particular, a refinement of Melfi's result. We also give a more detailed analysis of the special case p(n) = n 2 , looking at the subsets of n where s q (n) = s q (n 2 ) = k for fixed k.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 8 publications
(16 reference statements)
0
22
0
Order By: Relevance
“…In other words, can we say anything about #{n ≤ N | sq(n 2 ) sq (n) = a c } for some positive rational a c ? This has been done for the special case a c = 1 in [3] and [5]. This also leads to the major open question posed by Stolarsky of obtaining the average value of this ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, can we say anything about #{n ≤ N | sq(n 2 ) sq (n) = a c } for some positive rational a c ? This has been done for the special case a c = 1 in [3] and [5]. This also leads to the major open question posed by Stolarsky of obtaining the average value of this ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Notice n ≥ k + 2 because 3c < 6a and so 3c + 3 ≤ 6a so that 3(c − a) + 2 ≤ 3a − 1. By Lemma 3.10, we have for (u) 3 …”
Section: The Case Of R ≥mentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, in the case q = 2 (where S q (n) and N q (n) coincide), Stolarsky [20] proved that, for infinitely many n, N 2 (n 2 ) N 2 (n) ≤ 4 (log log n) 2 log n , a result that was subsequently substantially sharpened and generalized by Hare, Laishram and Stoll [13]. Further developments are well described in [14] where, in Date: October 12, 2018. 1991 Mathematics Subject Classification.…”
Section: Introductionmentioning
confidence: 93%
“…However, it is far from clear for which triples (k, ℓ, m) such solutions exist, or even more generally, whether there are finitely of infinitely many solutions in odd a, b for the system (1) for a given triple (k, ℓ, m). Part of the motivation to study (1) also comes from a paper of Hare, Laishram, Stoll [8] where the authors studied the solution set of the equation s(a 2 ) = s(a) = k, which is a particular instance of (1). For example, they showed that s(a 2 ) = s(a) = 8 only allows finitely many odd solutions a, whereas s(a 2 ) = s(a) = 12 has infinitely many odd solutions a.…”
Section: Introductionmentioning
confidence: 99%